Neural basis of motivational approach and withdrawal behaviors in neurodegenerative disease. Issue 9 (14th July 2015) - Shinagawa, Shunichiro; Babu, Adhimoolam; Sturm, Virginia; Shany‐Ur, Tal; Toofanian Ross, Parnian; Zackey, Diana; Poorzand, Pardis; Grossman, Scott; Miller, Bruce L.; Rankin, Katherine P.
Abstract: Introduction: The Behavioral Inhibition System (BIS) and the Behavioral Activation System (BAS) have been theorized as neural systems that regulate approach/withdrawal behaviors. Behavioral activation/inhibition balance may change in neurodegenerative disease based on underlying alterations in systems supporting motivation and approach/withdrawal behaviors, which may in turn be reflected in neuropsychiatric symptoms. Method: A total of 187 participants (31 patients diagnosed with behavioral variant of FTD [bvFTD], 13 semantic variant of primary progressive aphasia [svPPA], 14 right temporal variant FTD [rtFTD], 54 Alzheimer's disease [AD], and 75 older healthy controls [NCs]) were included in this study. Changes in behavioral inhibition/activation were measured using the BIS/BAS scale. We analyzed the correlation between regional atrophy pattern and BIS/BAS score, using voxel‐based morphometry (VBM). Results: ADs had significantly higher BIS scores than bvFTDs and NCs. bvFTDs activation‐reward response (BAS‐RR) was significantly lower than ADs and NCs, though their activation‐drive (BAS‐D) was significantly higher than in ADs. Both AD and rtFTD patients had abnormally low activation fun‐seeking (BAS‐FS) scores. BIS score correlated positively with right anterior cingulate and middle frontal gyrus volume, as well as volume in the right precentral gyrus and left insula/operculum. Conclusions: AD, bvFTD, and rtFTD patients show divergent patterns of change in approach/withdrawal reactivity. High BIS scores correlated with preservation of right‐predominant structures involved in task control and self‐protective avoidance of potentially negative reinforcers. Damage to these regions in bvFTD may create a punishment insensitivity that underlies patients' lack of self‐consciousness in social contexts. Abstract : Behavioral approach and withdrawal in NDG.